Development and delay analysis of data acquisition gateway for train monitoring and control system. (August 2019) - Yang, Weifeng; Guo, Songlin; Chen, Tao; Yao, Zikai
Abstract: To solve data processing for the train multiple monitoring and control devices, a multi-protocol data acquisition gateway based on the embedded Linux system was designed. The principle of the gateway was proposed. The gateway's communication abilities of RS485 network and Ethernet as well as RS485 network based on HDLC protocol and Ethernet were demonstrated by delay analysis for data propagation. The implementation of data acquisition and retransmission for the LKJ and TCMS provides support for achieving the aims of remote monitoring and fault diagnosis for rail transit train.